Edifice of polyphonic crescendo - Shabalala, Lwanele (School of Architecture, Planning and Geomatics, 2024)
A redefining of the built urban context in relation to the micro architectural devices implemented upon the city forms a robust intensity mediated through a series of thresholds and liminal spaces held together by a predetermined framework and artistic expression. These architectural devices set up conditions for contradictions that allow for spontaneous, chaotic polyphonic crescendos between social, economic, and infrastructural relationships. Importantly, these relationships within the context of cities cannot exist in isolation (Low, 2003) and form a complex framework in which we as the inhabitant assume to roles of actors, directors and set designers to collectively mould our environment (Harvey, 2003). A clear understanding of the reciprocal nature that exists between the human and the built form even though the latter can be argued not to overtly influence behaviour but rather a reaction towards it (Sfintes, 2012). Exploring concepts of how people and spatial environments interrelate to define their attitudes towards the ephemeral spaces of occupation and transition guided by a historical overview reveals an engendered bias and subjectivity to the perception of these spaces and their potential (Smith, 2001). Festival(temporal), event(spontaneous), contradictions(disturbance), context and socio-economic pressures influence an architectural typology that shapes the urban landscape that then becomes the setting for inhabitation for the various social interactions that dictate our apprehension of space and its' architectural framework. Guided by this, an artist's expression can then be generated in the material composition and harmonic cacophony of fluid spaces (Smith, 2001) to provide a sense of place to a space.